2019
DOI: 10.3897/nucet.5.39096
|View full text |Cite
|
Sign up to set email alerts
|

Different distributions of gold nanoparticles on the tumor and calculation of dose enhancement factor by Monte Carlo simulation

Abstract: Gold nanoparticles can be used to increase the dose of the tumor due to its high atomic number as well as being free from apparent toxicity. The aim of this study is to evaluate the effect of distribution of gold nanoparticles models, as well as changes in nanoparticle sizes and spectrum of radiation energy along with the effects of nanoparticle penetration into surrounding tissues in dose enhancement factor DEF. Three mathematical models were considered for distribution of gold nanoparticles in the tumor, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…AuNPs size [15,24,25,[29][30][31]34,[36][37][38][39], concentration [26,29,30,33,37,39] and the modelling of distribution [28,36,[38][39][40][41] are the main AuNPs properties under investigation in literature. Photon energy [12,22,[24][25][26]28,29,[31][32][33][34][36][37][38], the presence of flattening filter (FF) in clinical photon beams [15,27,30], simulation set up [42] and the user defined parameters [43] (Auger electrons activation, energy cut off, voxel size etc.) have been discussed in MC simulations from 2010 to 2019.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AuNPs size [15,24,25,[29][30][31]34,[36][37][38][39], concentration [26,29,30,33,37,39] and the modelling of distribution [28,36,[38][39][40][41] are the main AuNPs properties under investigation in literature. Photon energy [12,22,[24][25][26]28,29,[31][32][33][34][36][37][38], the presence of flattening filter (FF) in clinical photon beams [15,27,30], simulation set up [42] and the user defined parameters [43] (Auger electrons activation, energy cut off, voxel size etc.) have been discussed in MC simulations from 2010 to 2019.…”
Section: Resultsmentioning
confidence: 99%
“…In other studies, AuNPs size has a negligible effect in dose enhancement when photon energies are in MV range [29,30,[36][37][38]. More specifically, Pakravan et al [30] reported the greatest difference in DEF values of 1.046 and 1.056 in case of 25 nm diameter and 200 nm respectively for a concentration of 36 mg AuNPs g _1 tumor and a 6 MV photon beam.…”
Section: Sizementioning
confidence: 98%
“…Nevertheless, three studies have tried such straightforward simulation using the MCNP code and a hierarchical geometry with cubic voxels of decreasing size [17,20,44]. Spherical GNPs were placed in the centers of the lowest-level voxels that were filled with water.…”
Section: Comparison With Ders Reported In Literaturementioning
confidence: 99%
“…All three papers report an increase in the average DER with increasing GNP size for a constant MFG [17,20,44]. This dependence on GNP size appears to be an artefact of the simulation, as the results are not compatible with what one would expect from energy conservation: As was shown by Koger and Kirkby [43], the fraction of the energy transferred to electrons by soft X-ray photon interactions inside a GNP and imparted to water by these electrons decreases with increasing GNP size.…”
Section: Comparison With Ders Reported In Literaturementioning
confidence: 99%
See 1 more Smart Citation